Polycrystalline films of MAxMEA1−xPbI3 hybrid perovskites obtained by the solution method: Crystallization and morphology - Ryabko Andrey; Ovezov Maksat; Maximov Alexander; Permiakov Nikita; Tuchkovskiy Alexander; Vrublevskiy Igor; Muratova Ekaterina; Aleshin Andrey; Moshnikov Vyacheslav (St. Petersburg Polytechnical University Journal: Physics and Mathematics, 2025)
In this work, the morphological features of polycrystalline films of hybrid perovskites MAxMEA1−xPbI3 formed by a single-stage centrifugation method from DMF and DMSO solutions (4:1) have been investigated. The results of the studies showed that an increase in the proportion of monoethanolammonium in MAxMEA1−xPbI3 led not only to a change in the absorption spectra and an increase in the interplanar distances of the crystal lattice, but also to a significant change in the morphology of the films from elongated split crystallites to a uniform coating of nanocrystallites. An increase in the proportion of monoethanolammonium iodide in the solution also improved the wettability of solutions and the continuity of the coating of substrates with hybrid perovskite MAxMEA1−xPbI3 without additional surface activation processes. The increased band gap of MAxMEA1−xPbI3 compared to MAPbI3 makes these hybrid perovskites attractive for use in tandem solar cells.